Handbook of in Vivo Chemistry in Mice : From Lab to Living System - Tanaka, Katsunori; Vong, Kenward (Wiley-VCH, 2020)
Of Currently Available Mouse Models / Ami Ito, Namiko Ito, Kimie Niimi, Takashi Arai, Eiki Takahashi -- General Notes of Chemical Administration to Live Animals / Ami Ito, Namiko Ito, Takashi Arai, Eiki Takahashi, Kimie Niimi -- Optical-Based Detection in Live Animals / Mikako Ogawa, Hideo Takakura -- Ultrasound Imaging in Live Animals / Francesco Faita -- Positron Emission Tomography (PET) Imaging in Live Animals / Xiaowei Ma, Zhen Cheng -- Single-Photon Emission Computed Tomographic Imaging in Live Animals / Yusuke Yagi, Hidekazu Kawashima, Kenji Arimitsu, Koki Hasegawa, Hiroyuki Kimura -- Radiotherapeutic Applications / Koki Hasegawa, Hidekazu Kawashima, Yusuke Yagi, Hiroyuki Kimura -- Metabolic Glycan Engineering in Live Animals: Using Bio-orthogonal Chemistry to Alter Cell Surface Glycans / Danielle H Dube, Daniel A Williams -- In Vivo Bioconjugation Using Bio-orthogonal Chemistry / Maksim Royzen, Nathan Yee, Jose M Mejia Oneto -- In Vivo Targeting of Endogenous Proteins with Reactive Small Molecules / Naoya Shindo, Akio Ojida -- In Vivo Metal Catalysis in Living Biological Systems / Kenward Vong, Katsunori Tanaka -- Chemical Catalyst-Mediated Selective Photo-oxygenation of Pathogenic Amyloids / Youhei Sohma, Motomu Kanai -- Nanomedicine Therapies / Patrícia Figueiredo, Flavia Fontana, Hélder A Santos -- Photoactivatable Targeting Methods / Xiangzhao Ai, Ming Hu, Bengang Xing -- Photoactivatable Drug Release Methods from Liposomes / Hailey I Kilian, Dyego Miranda, Jonathan F Lovell -- Peptide Targeting Methods / Ruei-Min Lu, Chien-Hsun Wu, Ajay V Patil, Han-Chung Wu -- Glycan-Mediated Targeting Methods / Kenward Vong, Katsunori Tanaka, Koichi Fukase.